Molecular diversity and predictability of Vibrio parahaemolyticus along the Georgian coastal zone of the Black Sea - Haley, Bradd J.; Kokashvili, Tamar; Tskshvediani, Ana; Janelidze, Nino; Mitaishvili, Nino; Grim, Christopher J.; Constantin de Magny, Guillaume; Chen, Arlene J.; Taviani, Elisa; Eliashvili, Tamar; Tediashvili, Marina; Whitehouse, Chris; et al. (Frontiers in Microbiology, 2014)
Vibrio parahaemolyticus is a leading cause of seafood-related gastroenteritis and is also an autochthonous member of marine and estuarine environments worldwide. One-hundred seventy strains of V. parahaemolyticus were isolated from water and plankton samples collected along the Georgian coast of the Black Sea during 28 months of sample collection. All isolated strains were tested for presence of tlh, trh, and tdh. A subset of strains were serotyped and tested for additional factors and markers of pandemicity. Twenty-six serotypes, five of which are clinically relevant, were identified. Although all 170 isolates were negative for tdh, trh, and the Kanagawa Phenomenon, 7 possessed the GS-PCR sequence and 27 the 850 bp sequence of V. parahaemolyticus pandemic strains. The V. parahaemolyticus population in the Black Sea was estimated to be genomically heterogeneous by rep-PCR and the serodiversity observed did not correlate with rep-PCR genomic diversity. Statistical modeling was used to predict presence of V. parahaemolyticus as a function of water temperature, with strongest concordance observed for Green Cape site samples (Percent of total variance = 70, P < 0.001). Results demonstrate a diverse population of V. parahaemolyticus in the Black Sea, some of which carry pandemic markers, with increased water temperature correlated to an increase in abundance of V. parahaemolyticus.